PENGARUH DAYA TARIK PESAN PADA UNGGAHAN INSTAGRAM BILLBOARD 'SIAP MENJADI NOMOR 1' TERHADAP PENINGKATAN BRAND AWARENESS PREPP STUDIO - Nafal Hibrizi, (2021)
Prepp Studio is a local fashion brand that offers casual and simple product that can be used daily by people especially men. Prepp Studio has attractive marketing strategy, for example putting up billboard 'Siap Menjadi Nomor 1' with Arief Muhammad as the figure. This billboard getting quite interesting for people, especially after several big media account such as folkative and ussfeeds is posting about this billboard. This study will explain the relationship between the effect of message attractiveness on instagram's billboard 'Siap Menjadi Nomor 1' uploads towards the increase of Prepp Studio's brand awareness. This study uses affective-cognitive consistency theory that has an assumption if cognitive aspect has to be changed, affective aspect has to be changed first and ended with change of attitude as the result. The method used are quantitative with survey methods with 100 respondent that must follow folkative instagram account and aware of instagram's billboard 'Siap Menjadi Nomor 1' version 1 and 2 uploads. The results showed that there was 24,1 % effect of message attractiveness on instagram's billboard 'Siap Menjadi Nomor 1' uploads towards the increase of Prepp Studio's brand awareness. The hypothesis also shows that H0 is rejected and accepted H1. Based on the results, there is an effect of message attractiveness on instagram's billboard 'Siap Menjadi Nomor 1' uploads towards the increase of Prepp Studio's brand awareness.